FOURIER TRANSFORM INFRARED SPECTROSCOPIC (FT-IR) STUDY OF DICOFOL-INDUCED STRUCTURAL AND BIOCHEMICAL PERTURBATIONS ON RATTUS NORVEGICUS TESTIS. - GP, Manjunath; M., David (International Journal of Research -GRANTHAALAYAH, 2024)
Extensive industrial use and reputation as a pervasive environmental pollutant, organochlorine toxicity has received a lot of attention in recent years. In order to assess the organochlorine acaricide Dicofol’s (DCF) toxic effects on the rat reproductive system at the molecular level, the present study employed histopathological investigations and the FT-IR technique. Rats were randomly assigned to four groups C, D1, D2, and D3 for this purpose. For 90 days, each group was given 00, 5, 7, and 10 mg/100g of body weight. All of the FT-IR peaks and the histological analysis revealed a negligible change in the group that received lower doses of D1. The area under the peaks, which correspond to various biomolecules, significantly decreased in the groups treated with higher doses of D2 and D3. Furthermore, when comparing the testes of the D2 and D3 groups to the control group, histopathological analysis revealed mild to severe degenerative changes in seminiferous tubules at different dose levels. In summary, the higher dosage of dicofol that was chosen resulted in considerable testicular damage, which impacts male fertility. Consequently, the use of such an acaricide ought to be restricted to a planned program.